A dynamic coordinated control strategy of WTG-ES combined system for short-term frequency support. (April 2018) - Li, Yong; He, Li; Liu, Fang; Tan, Yi; Cao, Yijia; Luo, Longfu; Shahidehpour, Mohammod
Abstract: In this article, a dynamic coordinated control strategy is proposed for wind turbine generator (WTG) and energy storage (ES) combined system, which enables the combined system to participate in the short-term frequency regulation of the utility gird. The theoretical analysis of the equivalent inertia of the combined system is performed and the mechanism of the short-term frequency regulation is revealed. The coordinated control strategy is designed considering the variability of wind power and the state of charge (SoC) of ES, which ensures a good performance of the frequency support under the wind variation and the SoC changing. Case study is used to validate the proposed strategy, which indicates that, this strategy can adaptively adjust the power distribution between the WTGs and the ES units during the frequency support, keep the output power stable when the wind speed changes, and diminish the decrease of SoC of the ES units. Graphical abstract: Highlights: A coordinated control strategy of WTG-ES system is proposed for frequency support of utility grid. Characteristics of inertia and primary frequency regulation are taken into account. The control loop is designed considering the variation of wind speed and SoC.